(untitled) (Cambridge, 1985)
The essays in this volume provide an unusual historical perspective on the experience of illness: they try to reconstruct what being ill (from a minor ailment to fatal sickness) was like in pre-industrial society from the point of view of the sufferers themselves. The authors examine the meanings that were attached to sickness; popular medical beliefs and practices; the diffusion of popular medical knowledge; and the relations between patients and their doctors (both professional and 'fringe') seen from the patients' point of view. This is an important work, for illness and death dominated life in earlier societies to an enormous degree. Yet almost no studies of this kind have ever been carried out before, practically all previous treatments having been written from the traditional point of view of the doctor, the hospital, or medical science. It will accordingly interest a wide range of readers interested in social history as well as the history of medicine itself.
Keywords: Medicine,Health attitudes,Medicine,Y học,Thái độ y tế,Y khoa; Public opinion,History,History,History,Ý kiến công chúng,Lịch sử,Lịch sử,Lịch sử